Navigating Treatment in the Shadow of the Overdose Crisis: Perspectives of Youth Experiencing Street-Involvement Across British Columbia. (June 2022) - Thulien, Madison; Charlesworth, Reith; Anderson, Haleigh; Dykeman, Rainbow; Kincaid, Katey; Sedgemore, Kali; Knight, Rod; Fast, Danya
ABSTRACT: Objective: Youth experiencing street-involvement are particularly vulnerable to substance use-related harms. Since an overdose public health emergency was declared in British Columbia (BC) in 2016, there have been concerted efforts to expand youth's access to integrated mental health and substance use treatment across the province. The present study sought to explore how youth were navigating this rapidly evolving treatment landscape. Methods: Focus groups were conducted with youth experiencing street-involvement in three BC cities, followed by a summit event in Vancouver. Audio recordings were transcribed verbatim and coded thematically alongside observational field notes. All activities were undertaken in collaboration with a Youth Advisory Council. Results: Across BC, youth expressed desires to achieve aspects of what some called a "normal life" following treatment, which required having "somewhere to go next." In the absence of desirable housing and adequate income, youth were often left with the crushing sense that, despite their efforts, treatment would not ultimately help them to "get somewhere better." Negative experiences in treatment settings were also shaped by the files that "followed" youth across care settings, inappropriate information sharing between providers, and an overemphasis on pharmacotherapies (namely, opioid agonist therapies and psychotropic medications). Conclusion: Our findings point to the inability of existing services and systems to address entrenched marginalization and chronic instability. Our findings also underscore the importance of relationship-, trust-, and future-building to providing treatment and care to youth. Young people must be empowered with control over their treatment trajectories, including decision-making surrounding pharmacotherapies and information sharing. Abstract : Objectif: Les jeunes de la rue sont particulièrement vulnérables aux méfaits de la consommation de substances psychoactives. Depuis que le problème de surdoses a été déclaré comme une urgence de santé publique en Colombie-Britannique (C.-B.) en 2016, des efforts concertés ont été déployés pour améliorer l'accès des jeunes aux traitements intégrés de santé mentale et de consommation dans toute la province. La présente étude vise à explorer la façon dont les jeunes s'orientent dans ce contexte de traitement en constante évolution. Méthodologie: Des groupes de discussion ont été menés avec des jeunes de la rue dans trois villes de la Colombie-Britannique, suivis d'un sommet à Vancouver. Les enregistrements audio ont été transcrits textuellement et classés par thèmes avec les notes d'observation sur le terrain. Toutes les activités ont été réalisées avec la collaboration d'un conseil consultatif des jeunes. Résultats: Partout en Colombie-Britannique, les jeunes ont exprimé le désir de mener une « vie normale » après le traitement, ce qui implique d'avoir « quelque part où aller par la suite ». Sans logement ni revenu adéquats, les jeunes ont souvent le sentiment accablant que, malgré leurs efforts, ultimement, le traitement ne les aidera pas à « aller mieux ». Les expériences négatives dans les milieux de traitement étaient également liées aux dossiers qui « suivent » les jeunes dans différents contextes de soins, au partage inapproprié de renseignements entre les fournisseurs et à une insistance excessive sur les pharmacothérapies (à savoir, les traitements par agonistes opioïdes et les médicaments psychotropes). Conclusions: Nos constatations soulignent l'incapacité des services et systèmes existants à lutter contre la marginalisation profondément ancrée et l'instabilité chronique, de même que l'importance de miser sur les relations, la confiance et une vision tournée vers l'avenir pour offrir des traitements et des soins aux jeunes. Les jeunes doivent être outillés pour contrôler leur cheminement thérapeutique, y compris au regard des décisions sur la pharmacothérapie et le partage de renseignements.